Barriers and Overcoming Strategies for Lean Construction Implementation in Ethiopia: An Integrated Fuzzy AHP and Fuzzy TOPSIS Framework (Advances in Civil and Architectural Engineering, 2025)
Lean construction (LC) is a valuable concept for waste reduction and project performance improvement. There is awareness of LC principles and tools among professionals and limited use in Ethiopian projects. However, adoption and implementation are still low. This study aims to identify and prioritize barriers and strategies for overcoming them to successfully implement LC in the industry. This study uses a multi-criteria decision-making (MCDM) approach by integrating the fuzzy analytical hierarchy process (AHP) and the fuzzy technique for order of preference by similarity to the ideal solution (TOPSIS). A review of the published articles along with expert guidance identified 28 barriers grouped into six categories. Furthermore, nine alternative strategies were proposed to address these barriers. The fuzzy AHP is used to determine the weights of the barriers as criteria, and the fuzzy TOPSIS method is used to obtain the final ranking of the overcoming strategies for LC implementation (LCI). The top four barriers hindering the smooth implementation of LC were "resistance to change", "lack of knowledge in lean", "lack of long-term philosophy", and "lack of government support". The most effective overcoming strategies were leadership and management, cultural change for continuous learning and improvement, and education and training. The study's sensitivity analysis robustness test confirmed the robustness and usefulness of the findings, which provides strategic insight for decision-makers and guides professionals to plan effective LC adoption.